2007
DOI: 10.1364/oe.15.006464
|View full text |Cite
|
Sign up to set email alerts
|

High energy, single-mode, narrow-linewidth fiber laser source using stimulated Brillouin scattering beam cleanup

Abstract: energy, single-mode, narrow-linewidth fiber laser source using stimulated Brillouin scattering beam cleanup. Optics Express, Optical Society of America, 2007, 15 (10) Abstract:We propose an original nonlinear beam cleaning fiber laser architecture to obtain high energy pulses with a good beam quality and a narrow linewidth. The output beam of a large core Er:Yb co-doped multimode fiber amplifier (M 2 ~ 6, 220 µJ) is converted into a near diffraction limited beam (M 2 = 1.6) through a stimulated Brillouin scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 11 publications
0
14
2
Order By: Relevance
“…In 1993, H. Bruesselbach firstly reported that Stimulated Brillouin Scattering (SBS) in multimode fiber leads to the event of beam cleanup [2] , which can purify multimode beam to fundamental beam, and several follow-up studies was evoked [3][4][5][6][7][8] . Lombard and Brignon achieved beam cleanup in GI multimode fiber by using a self-aligned Brillouin cavity, under the conditions of 65μm core diameter and 150W peak power, in 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In 1993, H. Bruesselbach firstly reported that Stimulated Brillouin Scattering (SBS) in multimode fiber leads to the event of beam cleanup [2] , which can purify multimode beam to fundamental beam, and several follow-up studies was evoked [3][4][5][6][7][8] . Lombard and Brignon achieved beam cleanup in GI multimode fiber by using a self-aligned Brillouin cavity, under the conditions of 65μm core diameter and 150W peak power, in 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Brillouin scattering in fibers has attracted lots of attention for its potential usage in sensing [1], single mode amplification [2], multi-wavelength fiber lasers [3] and slow light [4]. Therefore, a lot of research works on Brillouin scattering in fibers have been done and reported in theory and experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Very large core fibers have demonstrated their ability to achieve very high energies without any onset of SBS, but to the detriment of the beam quality. In order to convert the multimode output beam of a large core fiber amplifier into a single mode beam, nonlinear beam cleaning techniques such as Raman [2] or Brillouin scattering [3][4][5][6] in multimode fibers have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%